Prioritization of Selection Criteria for Sustainable Materials and Equipment in Construction Projects by Managing Energy Consumption Using TOPSIS Method - Ashkan Khoda Bandeh Lou (Journal of Global Pharma Technology, 2017)
The use of conventional construction methods and considering the new technologies in this regard as well as using sustainable materials and equipment are inevitable to strengthen the constructions, achieving sustainable development, and improving living conditions. Choosing a suitable construction system due to the high uncertainties in the decision-making process is very complex. On the other hand, the knowledge of very broad construction systems has a structured weakness, which includes a variety of specialties. Hence, choosing sustainable equipment and materials in construction projects is an essential solution for designing and implementing an appropriate construction system using Multiple Criteria Decision Making. This research aims to determine and facilitate a criterion for equipment and material selection based on sustainability and productivity management approach in energy consumption in construction projects. Then, some of the important factors, which affect the decisions of engineers and designers in the selection of materials for sustainable design and energy management, are characterized by analyzing the information. Modeling will be used to evaluate and choose the most appropriate materials, which aims to provide an analytical decision support tool for achieving the goals of sustainable design in TOPSIS. Keywords: Project Management, Equipment Selection, Sustainable Materials, Multi-Criteria Decision Making, Topsis.